Pengaruh Financial Distress Dan Ukuran Kap Terhadap Kualitas Audit - rizqa rahman (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2021)
Business processes and accounting standards are becoming more complex. The role of public accountants is not optimal in detecting and preventing business continuity problems. The audit opinion has not been able to show the actual condition of the company. Whereas, high quality audits can provide good information in decision making by management, creditors, or investors. This study aims to examine whether using Big 4’s audit service are more excellent than others. Sample in this study is Indonesia State Owned Enterprises that listed in Indonesia Stock Exchange from 2015 to 2018. We use regression test and t- test as analyses technique. We finds that Big 4 have delivered better audit quality than others.